PENGARUH KEMAMPUAN INOVASI PRODUK TERHADAP KINERJA PEMASARAN : PERAN DIFERENSIASI PRODUK (Studi pada Industri Pangan Lokal Enbal di Kabupaten Maluku Tenggara) - Arnol Alfyan Rangotwat (Manis: Jurnal Manajemen dan Bisnis, 2018)
Local food industry in Indonesia has become the belle of the uniquenessor distinctiveness of each region of the country's remote areas. Of course, byintroducing diverse cultures based on local wisdom, local food as one partregardless separated from the increase in the country's economy, especially in thevarious regions in Indonesia. The purpose of this study was to determine andanalyze the effect of product innovation capabilities on product differentiation andproduct differentiation influence on the performance of marketing. This type ofresearch is inferential with a quantitative approach. Sampling was done by usingNon-Probability or purposive sampling a total of 120 samples. Collecting datausing questionnaires as research instrument. Data analysis using descriptiveanalysis and test equipment used is Path Analysis.Hypothesis testing using the Ftest and t test. The results showed that (1) there is a significant and positive effectof product innovation capabilities on product differentiation; (2) there is a positiveand significant effect on the performance of product differentiation marketing.The values R2 is found to be 0.934, which means the amount of exogenousvariables on endogenous variables by 93.4%.